Analysis of Risk Factors for Bleeding and Recurrence of Ovarian Endometriomas after Laparoscopic Surgery and Its Impact on Pregnancy Outcomes - Juanjuan Han; Lin Zheng (IMR Press, 2024)
Background: Ovarian endometriomas are a common gynecological disease in women of childbearing age. Laparoscopic surgery is the gold standard surgical procedure for treating patients with ovarian endometriomas. However, laparoscopic postoperative bleeding, recurrence, and pregnancy failure are still unavoidable problems for many patients. Methods: A retrospective analysis was performed of 212 patients with ovarian endometriomas treated by laparoscopic surgery in our hospital from January 2016 to December 2020, with postoperative follow-up for 2 years. The researchers completed the follow-up by telephone, email, and outpatient review. Chi-square test was used to analyze the relationship between their clinical characteristics and postoperative bleeding, recurrence, and pregnancy along with logistic regression analysis of the risk factors for postoperative bleeding and recovery. Also, the use of logistic regression analysis may influence the factors influencing pregnancy outcome after laparoscopy. Results: The postoperative pregnancy success rate in 212 patients with ovarian endometriomas was 63.7%. The incidence of bleeding after surgery was 31.6% and the recurrence rate was 21.2%. The results of the logistic-regression analysis demonstrated that, age (odds ratio (OR) = 1.208, p = 0.001), combined with deep infiltrating endometriosis (DIE) (OR = 5.18, p = 0.023), cystic diameter ≥5 cm (OR = 0.076, p = 0.005), bleeding during the operation ≥50 mL (OR = 25.769, p = 0.000) and intraoperative bleeding (OR = 1.295, p = 0.000) were independent risk factors for postoperative bleeding. Severe dysmenorrhea (OR = 6.189, p = 0.004), cystic diameter ≥5 cm (OR = 8.502, p = 0.001), bilaterality (OR = 85.214, p = 0.001) and intraoperative bleeding (OR = 0.911, p = 0.003) were independent risk factors for the recurrence of ovarian endometriomas. By logistic regression analysis, age, bilaterality, the revised American Fertility Society (r-AFS) stage ≥Ⅲ were all related factors for postoperative pregnancy (p < 0.05). Conclusions: Age, combined with deep infiltrating endometriosis, cystic diameter, bleeding during the operation and intraoperative bleeding were all independent risk factors for postoperative bleeding. Severe dysmenorrhea, bilaterality, cystic diameter and intraoperative bleeding were independent risk factors for the recurrence of ovarian endometriomas. Age, bilaterality, r-AFS stage ≥Ⅲ were related factors for postoperative pregnancy.